Blood and Salivary Amphiregulin Levels as Biomarkers for Asthma - Hachim, Mahmood Yaseen; Elemam, Noha Mousaad; Ramakrishnan, Rakhee K.; Salameh, Laila; Olivenstein, Ronald; Hachim, Ibrahim Yaseen; Venkatachalam, Thenmozhi; Mahboub, Bassam; Al Heialy, Saba; Halwani, Rabih; Hamid, Qutayba; Hamoudi, Rifat (Frontiers in Medicine, 2020)
Background: Amphiregulin (Areg) expression in asthmatic airways and sputum was shown to increase and correlate with asthma severity. However, no studies were carried out to evaluate the Areg level in blood and saliva of asthmatic patients. Objective: To measure circulating Areg protein concentrations in blood and saliva from asthmatic patients and correlate its levels with asthma severity. Methods: Plasma and Saliva Areg protein concentrations were measured using ELISA in mild, moderate, and severe asthmatic patients compared to healthy controls. Primary asthmatic bronchial epithelial cells and fibroblasts were assessed for Areg mRNA expression and soluble Areg in their conditioned media. Tissue expression of Areg was evaluated using immunohistochemistry of bronchial biopsies from asthmatic patients and healthy controls. Results: Asthmatic patients had higher Areg protein levels in blood and saliva compared to control subjects. Higher mRNA expression in primary bronchial epithelial cells and higher Areg immunoreactivity in bronchial biopsies were also observed. Both blood and saliva Areg levels showed positive correlations with allergic rhinitis status, atopy status, eczema status, plasma periostin, neutrophilia, Montelukast sodium use, ACT score, FEV1, and FEV1/FVC. Areg levels can differentiate the healthy controls from non-severe asthmatic subjects with good sensitivity and specificity. Conclusion: Areg levels measured in a minimally-invasive blood sample and a noninvasive saliva sample of asthmatic patients can serve as a putative asthma biomarker. Clinical Implications This is the first report to suggest the ability of blood and saliva Areg levels to differentiate between healthy and asthmatic subjects. Therefore, Areg could be used as an adjunct bedside biomarker to support the diagnosis of asthma, specifically in non-severe cases.